Oxytelus sishuishanus, a new species of Oxytelus Gravenhorst, 1802 (Coleoptera: Staphylinidae: Oxytelinae) from Sishui Mountain, China - Ma, Hong-Ye; Wang, Lin-Fei; Lü, Liang (Zootaxa, 2024)
A new species, Oxytelus sishuishanus Lü, is described from Hunan, China. This species closely resembles O. ailaoshanicus Lü & Zhou, 2012, but can be distinguished by the male clypeus, which is not so protruding as in O. ailaoshanicus, and by the symmetrically mirrored apical forking of the aedeagal parameres.